TECHNICAL EFFICIENCY AND PRODUCTION SCALE ANALYSIS IN SMALL-SCALE TUNA HANDLINE FISHERIES IN WEST SULAWESI - Hatmar, Muh Aldhy; Nelwan, Alfa (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
Tuna fishing activity in West Sulawesi has intensified in recent years, raising concerns regarding the sustainability of the fishery in the Makassar Strait amid increasing fishing pressure. This study evaluates the capacity utilization and resource use efficiency of small-scale handline vessels by measuring their technical and scale efficiency. A total of 78 tuna handline vessels were analyzed using an output-oriented Data Envelopment Analysis (DEA) model under Variable Returns to Scale (VRS), covering two vessel categories: